UvrD Participation in Nucleotide Excision Repair Is Required for the Recovery of DNA Synthesis following UV-Induced Damage in Escherichia coli - Kelley N. Newton; Charmain T. Courcelle; Justin Courcelle (Journal of Nucleic Acids)
UvrD is a DNA helicase that participates in nucleotide excision repair and several replication-associated processes, including methyl-directed mismatch repair and recombination. UvrD is capable of displacing oligonucleotides from synthetic forked DNA structures in vitro and is essential for viability in the absence of Rep, a helicase associated with processing replication forks. These observations have led others to propose that UvrD may promote fork regression and facilitate resetting of the replication fork following arrest. However, the molecular activity of UvrD at replication forks in vivo has not been directly examined. In this study, we characterized the role UvrD has in processing and restoring replication forks following arrest by UV-induced DNA damage. We show that UvrD is required for DNA synthesis to recover. However, in the absence of UvrD, the displacement and partial degradation of the nascent DNA at the arrested fork occur normally. In addition, damage-induced replication intermediates persist and accumulate in uvrD mutants in a manner that is similar to that observed in other nucleotide excision repair mutants. These data indicate that, following arrest by DNA damage, UvrD is not required to catalyze fork regression in vivo and suggest that the failure of uvrD mutants to restore DNA synthesis following UV-induced arrest relates to its role in nucleotide excision repair.